Pengaruh Motivasi dan Lingkungan Kerja Terhadap Kinerja Karyawan Bagian Produksi Pada CV. Ubud Corner di Gianyar - Putri, Ni Putu Pramesti; Yayati Wilyadewi, Ida I Dewa Ayu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study is to find out the influence of motivation and work environment on the performance of production employees on the CV. Ubud Corner in Gianyar partially and simultaneously. In this study the data collection methods used were observations, interviews, documentation and questionnaires. The population in this study was 60 employees of the production department. The sample used in this study was as many as 60 respondents, using saturated sampling methods. The data analysis technique used in this study is Multiple Linear Regeresi Analysis. From the results of the study obtained the results that: Motivation has a positive and significant partial effect on employee performance. The work environment has a positive and significant effect on employee performance. Motivation and work environment have a positive and significant effect simultaneously on the performance of production employees on the CV. Ubud Corner in Gianyar. Leaders should be able to provide more motivation to employees by giving awards to outstanding employees. Leaders should also pay attention to the work environment so that employees feel comfortable at work. This means that motivation and work environment have a positive effect on employee performance.